2020
DOI: 10.1142/s1793292020500964
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Biomass-Derived N, S Co-doped Carbon with Hierarchically Porous Architecture for High Performance Supercapacitor

Abstract: Multi-element doped porous carbon materials are considered as one of the most promising electrode materials for supercapacitors due to their large specific surface area, abundant mesoporous structure, heteroatom doping and good conductivity. Herein, we propose a very simple and effective strategy to prepare nitrogen, sulfur co-doped hierarchical porous carbons (N-S-HPC) by one-step pyrolysis strategy. The effect of sole dopants as a precursor was a major factor in the transformation process. The optimized N-S-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 67 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…An increase in current densities accompanied by a decrease in charge and discharge time meant that the time for ion diffusion was shortened, which led to a decrease in specific capacitance. Table illustrates the specific capacitance values of the same type of material reported in the previous studies, which intuitively reflected the advantage of ACG-N-P-Ni. ,, The CV test for 3000 cycles performed for cycling stability of ACG-N-P-Ni under scanning conditions of 20 mV s –1 was investigated. Figure g reveals the curves of the sample at the 1st and 3000th laps.…”
Section: Findings and Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…An increase in current densities accompanied by a decrease in charge and discharge time meant that the time for ion diffusion was shortened, which led to a decrease in specific capacitance. Table illustrates the specific capacitance values of the same type of material reported in the previous studies, which intuitively reflected the advantage of ACG-N-P-Ni. ,, The CV test for 3000 cycles performed for cycling stability of ACG-N-P-Ni under scanning conditions of 20 mV s –1 was investigated. Figure g reveals the curves of the sample at the 1st and 3000th laps.…”
Section: Findings and Discussionmentioning
confidence: 87%
“…It could be seen in the Ragone diagram shown in Figure 7c that ACG-N-P-Ni//ACG-N-P-Ni provided excellent energy as well as power density (density of energy of 12.32 W h kg −1 with a density of power of 499.99 W kg −1 ) significantly better than previously reported supercapacitors. 4,20,49,51,52 Following 5000 charge−discharge cycling, the supercapacitor exhibited a high capacitance retention rate at 86.1% in Figure 7d, which demonstrated its remarkable cycling stability.…”
Section: Supercapacitors' Performancementioning
confidence: 98%
“…33 In the Raman spectrum (Figure 3b), D peaks (defects and disordered parts of the carbon structure) close to 1350 cm −1 were identified as well as G peaks (ordered crystal structure, that is, the degree of graphitization) around 1575 cm −1 . 34 The ratio of D peak to G peak (I D /I G ) has been commonly adopted to show the degree of graphitization of a material. The I D /I G ratios of AMT, AMT-Fe, AMT-B, and AMT-B-Fe reached 0.79, 0.85, 0.87, and 0.90, respectively, which indicated that the doping of B and Fe made the material produce a defect structure, thereby agreeing with the XRD test results.…”
Section: Resultsmentioning
confidence: 99%
“…In the Raman spectrum (Figure b), D peaks (defects and disordered parts of the carbon structure) close to 1350 cm –1 were identified as well as G peaks (ordered crystal structure, that is, the degree of graphitization) around 1575 cm –1 . The ratio of D peak to G peak ( I D / I G ) has been commonly adopted to show the degree of graphitization of a material.…”
Section: Resultsmentioning
confidence: 99%